Binding of LncDACH1 to dystrophin impairs the membrane trafficking of Nav1.5 protein and increases ventricular arrhythmia susceptibility - Genlong Xue; Jiming Yang; Yang Zhang; Ying Yang; Ruixin Zhang; Desheng Li; Tao Tian; Jialiang Li; Xiaofang Zhang; Changzhu Li; Xingda Li; Jiqin Yang; et al. (eLife)
Dystrophin is a critical interacting protein of Nav1.5 that determines its membrane anchoring in cardiomyocytes. Long noncoding RNAs (lncRNAs) are involved in the regulation of cardiac ion channels, while their influence on sodium channels remains unexplored. Our preliminary data showed that lncRNA-Dachshund homolog 1 (lncDach1) can bind to dystrophin, which drove us to investigate if lncDach1 can regulate sodium channels by interfering with dystrophin. Western blot and immunofluorescent staining showed that cardiomyocyte-specific transgenic overexpression of lncDach1 (lncDach1-TG) reduced the membrane distribution of dystrophin and Nav1.5 in cardiomyocytes. Meanwhile, peak INa was reduced in the hearts of lncDach1-TG mice than wild-type (WT) controls. The opposite data of western blot, immunofluorescent staining and patch clamp were collected from lncDach1 cardiomyocyte conditional knockout (lncDach1-cKO) mice. Moreover, increased ventricular arrhythmia susceptibility was observed in lncDach1-TG mice in vivo and ex vivo. The conservative fragment of lncDach1 inhibited membrane distribution of dystrophin and Nav1.5, and promoted the inducibility of ventricular arrhythmia. Strikingly, activation of Dystrophin transcription by dCas9-SAM system in lncDach1-TG mice rescued the impaired membrane distribution of dystrophin and Nav1.5, and prevented the occurrence of ventricular arrhythmia. Furthermore, lncDach1 was increased in transaortic constriction (TAC) induced failing hearts, which promoted the inducibility of ventricular arrhythmia. And the expression of lncDach1 is regulated by hydroxyacyl-CoA dehydrogenase subunit beta (hadhb), which binds to lncDach1 and decreases its stability. The human homologue of lncDACH1 inhibited the membrane distribution of Nav1.5 in human iPS-differentiated cardiomyocytes. The findings provide novel insights into the mechanism of Nav1.5 membrane targeting and the development of ventricular arrhythmias.